The Collateral Effects of COVID-19 Pandemic on the Status of Carbapenemase-Producing Pathogens - Ayoub Moubareck, Carole; Hammoudi Halat, Dalal (Frontiers in Cellular and Infection Microbiology, 2022)
The serious challenge of antimicrobial resistance continues to threaten public health and lingers in the era of the coronavirus disease 2019 (COVID-19), declared pandemic by the World Health Organization. While the pandemic has triggered the importance of infection control practices and preventive measures such as physical distancing, hand hygiene, travel reduction and quarantine, the ongoing alarm of antimicrobial resistance seems to accompany the pandemic too. Antimicrobial resistance has been fostered during COVID-19, possibly due to high rate of empirical antibiotic utilization in COVID-19 patients, increased use of biocides, and the disruption of proper healthcare for other conditions. Specifically, carbapenemase-producing Gram-negative bacteria have shown to cause secondary bacterial infections in patients hospitalized for COVID-19. Clinical and microbiological evidence of such infections is accumulating in different parts of the world. With the resilient nature of carbapenemases, their association with mortality, and the limited treatment options available, concerns regarding this group of antibiotic-hydrolyzing enzymes during the pandemic are expected to upsurge. While the additional burden carbapenemases exert on healthcare is worrisome, it remains hidden or abandoned among the various health consequences of the pandemic. The purpose of this minireview is to shed a light on carbapenemase-associated infections during such unprecedented time of COVID-19. A focused insight shall be made into carbapenemases, their implications for COVID-19 patients, and the features and consequences of co-infection, with a review of available evidence from pertinent literature. The importance of increased surveillance for carbapenemase-producers and optimizing their management in relation to the pandemic, shall be addressed as well.